At the beginnings of the funerary Megalithism in Iberia at Campo de Hockey necropolis - Eduardo Vijande-Vila; Marta Díaz-Zorita Bonilla; Berta Morell-Rovira; Íñigo Olalde; Lydia P. Sánchez-Barba Muñoz; Salvador Domínguez-Bella; Steven D. Emslie; Serafín Becerra-Martín; Ángel Rubio-Salvador; Diego Salvador Fernández-Sánchez; Juan Jesús Cantillo-Duarte; Inmaculada Alemán-Aguilera; et al. (Scientific Reports, 2022)
Abstract The excavations undertaken at the Campo de Hockey site in 2008 led to the identification of a major Neolithic necropolis in the former Island of San Fernando (Bay of Cádiz). This work presents the results of the latest studies, which indicate that the site stands as one of the oldest megalithic necropolises in the Iberian Peninsula. The main aim of this work is to present with precision the chronology of this necropolis through a Bayesian statistical model that confirms that the necropolis was in use from c. 4300 to 3800 cal BC. The presence of prestige grave goods in the earliest and most monumental graves suggest that the Megalithism phenomenon emerged in relation to maritime routes linked to the distribution of exotic products. We also aim to examine funerary practices in these early megalithic communities, and especially their way of life and the social reproduction system. As such, in addition to the chronological information and the Bayesian statistics, we provide the results of a comprehensive interdisciplinary study, including anthropological, archaeometric and genetic data.